Development of a Classification of Leisure Participation (CLP) Scale: Perceptions of leisure activities of women with and without chronic conditions - Khemthong, Supalak; Packer, Tanya; Passmore, Anne; Dhaliwal, Satvinder (2005)
Background: A number of theories address the role of leisure participation in health-related quality of life (Coleman and Iso-Ahola 1993; Passmore 2003), but most leisure studies have measured frequency of leisure participation without examining the role of different types of leisure. In addition, no studies have examined the perceptions of people with chronic conditions with regards to their classification of leisure activities. This is of importance as it is known that chronic conditions interrupt leisure participation especially in women (Zimmer, Hickey et al. 1995; Australian Bureau of Statistics 2001; Zoerink 2001). Women with and without chronic conditions may have different perceptions of the role of different activities and thus the classification of leisure activities. Because it is has been proposed that certain types of leisure activities, such as physical or social leisure, might be used as the basis of intervention for women with chronic conditions, perceived classification is important. This pilot study aimed to compare those perceptions of women with and without chronic conditions. The outcomes from this study will help in the development of the Classification of Leisure Participation (CLP) Scale.Method: This study recruited 24 women with and 24 women without chronic conditions aged between 25 and 64 to participate in a telephone survey. A random sample of women without chronic conditions was recruited and administered the survey by a phone marketing company. Women with chronic conditions were recruited via radio and newsletters, and later contacted by the phone marketing company. The survey contained 61 leisure activities, generated from previous studies. Participants were asked to classify each activity by indicating whether each activity represented mostly physical, social, educational/creative, or passive leisure.Analysis: Demographic data for both groups were tested for differences using independent T Tests and Chi-square Tests. Items which achieved 60% agreement on one of the four domains, were selected and included in a cluster analysis. The resultant dendrograms, identified the most representative items for each domain for each group of women.Results: The mean (SD) age of women with and without chronic conditions were 49.83 (10.96) and 48.21 (10.72). No significant differences were found between the two groups on the demographic variables of age, education level, and marital status. Different dendrograms emerged for the two groups. Women with chronic conditions agreed on 41 items in three domains whereas those without chronic conditions agreed on only 29 items divided into four domains.Conclusion: Different classifications of leisure participation were found. Women with chronic conditions view many more activities as physically demanding than those without. They do not classify any activities as educational/creative. Living with a chronic condition appears to alter perceptions of the demands and rewards of participating in activities. This has important implications for future studies of interventions. It also provides useful information for the development of a scale for measuring the effectiveness of interventions that aim to improve quality of life through engagement in meaningful leisure activities.